Telomerase activation cooperates with inactivation of p16 in early head and neck tumorigenesis - Soria, J C (Nature Publishing Group, 2001)
Alteration of the p16/pRb pathway may cooperate with telomerase activation during cellular immortalization and tumour progression. We studied p16 expression status by immunohistochemistry and telomerase activity using the TRAP assay in 21 premalignant lesions of the head and neck epithelium as well as 27 squamous-cell carcinomas. We also examined expression of other components of the pathway (cyclin D1 and pRb) as well as presence of human papillomavirus genomes which can target these molecules. 4 of 9 mild dysplastic lesions (44%), 8 of 12 moderate/severe dysplastic lesions (67%), and 25 of 27 squamous-cell carcinomas (92%) demonstrated high telomerase activity (P = 0.009). There was a parallel increase with severity of lesions for the trend in proportions of cases demonstrating p16 inactivation or cyclin D1 overexpression (P = 0.02 and P = 0.01, respectively). For Ki67, a marker of cell proliferation, this trend was not significant (P = 0.08). Human papillomavirus infection was only found in 4 cases among the 48 samples tested (8.3%). In conclusion, progression of disease is accompanied by a parallel and continuous increase in telomerase activity and alterations in cell cycle regulators (p16, cyclin D1), as proposed by in vitro models. © 2001 Cancer Research Campaign http://www.bjcancer.com